Pemetaan Tipologi Respon Buruh Kreatif terhadap Prekaritas Neoliberal melalui LEGO® Serious Play® - Moch. Shobastian Mahendra Muchtar; Yuyun Agus Riani (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2026)
Indonesia's creative industry significantly contributes to economic growth and cultural production, yet creative workers face precarious conditions: contractual insecurity, income volatility, project-based employment, and limited labor protection. This study maps a typology of creative labor responses to neoliberal precarity through an Critical Organizational Communication lens, examining how organizational discourses of flexibility, passion, creativity, and self-development function as communicative mechanisms reproducing neoliberal power and shaping worker subjectivities. Using Foucault's governmentality framework, it analyzes how discursive formations normalize precarity while enabling adaptation, negotiation, and reflexive resistance. A qualitative interpretive-critical approach was applied through play-based focus group discussions using LEGO® Serious Play® with ten creative workers. Confirmation interviews and SINDIKASI reports strengthened contextual interpretation. Symbolic model building and narrative interaction reveal patterned communicative orientations from adaptive resilience to subtle resistance. Organizational discourse constitutes precarious worker subjectivities, while participatory spaces enable collective meaning-making and reflexive agency.